Seasonal and body size-dependent variability in the bioaccumulation of PAHs and their alkyl homologues in pearl oysters in the central Arabian Gulf. (October 2022) - Soliman, Yousria; Wade, Terry L.; Sericano, Jose L.; Al Ansari, Ibrahim
Abstract: Spatiotemporal concentration patterns for 19 parents and their alkyl homologues were measured in Pinctada radiata from 7 locations in the central Arabian Gulf around Qatar in the winter, spring and summer (2014–2015). The concentrations of PAHs ranged from 20 to 2240 (262 ± 38.0 ng·g −1 dw) with the highest occurrence in the Doha harbor (738.4 ± 197.3 ng·g −1 dw) and the lowest in the west coast of Qatar (48.3 ± 5.8 ng·g −1 dw). Residual PAHs in the oysters were about two times higher in winter than in spring and summer (P < 0.05). PAHs in oysters are dominated by 2 and 3 rings PAHs and their alkyls. Alkylated PAHs (APAHs) comprised >55 % of the ΣPAHs. Statistically significant differences in PAHs profiles among oysters were due in part to differences in lipid contents and shell biometrics. Principal component analysis (PCA) and diagnostic ratios for sources identifications suggested that PAHs accumulations in oysters were due to petrogenic and fuel combustion. Graphical abstract: Unlabelled Image Highlights: Spatiotemporal distribution and levels of 43 PAHs were investigated in the Gulf. Levels of ∑43 PAHs in the winter were ca. 2 times levels in spring and summer 2- and 3-rings PAHs and their alkyls predominated in most site. Body size and lipid content are influential conditioners in PAHs bioaccumulation PAHs in oysters originated from mixed petroleum and combustion sources.